Principles of good governance in Islam - Azram, Mohammad (IIUM Press, 2012)
The first impression and the main thesis of this chapter is that the Qur’an does not teach us the art of slavery; it only teaches us the art of good governance: It is a different matter though that the Muslims are busy in reversing this process. The overriding objective of Islam is to establish a just socio-moral and economic-political order in this world. The Prophet (SAW) announced his Prophetic mission (in 610 C.E.) with social reforms such as the amelioration of the downtrodden,the have-nots in general, poor and the destitute, women, orphans, slaves, etc. were central to his mission (Nadwi, 1982). Both the Prophet (SAW) himself and his Meccan opponents were thoroughly convinced that if Islam were to unfold and implement itself in letter and spirit, it would entail a complete and comprehensive change of the existing (socio-moral and political) order. The Prophet (SAW) left Mecca for Madina (in 622 C.E.) and there he immediately assumed the managing of religio-political affairs of Madina (Bu ti, 1991). Here he initiated good governance by introducing social reforms (such as imposing Zakat for the betterment of the depressed layers of the society, rescuing the poor from chronic debts, to improve the defence of the new-born city-state, allotting shares in inheritance to women, regulating marriage and divorce, prohibiting usury and so forth), along with the promulgation of religio-moral and spiritual teachings of the Qur’an (such as the exclusive worship of God alone,and a firm faith in eschatology, that is, the day of judgment and the life hereafter). When people witnessed Islam being translated in practice and a just socio-moral order established, they entered the fold of Islam tribe after tribe so much so that when the Prophet (SAW) died (in June 632 C.E.) he was virtually a prophet-ruler of the entire Arabian Peninsula. In spite of that, the Prophet (SAW) never claimed himself to be a ruler, nor did he ever claim to be a ruler whose rule was under his Prophethood. He just claimed to be a Prophet; yet he was a ruler nonetheless. What does it mean? It means that in Islam the relationship between the state and religion is not like that of two sisters, one helping the other. In fact, the state viewed in isolation, is nothing but a reflection of all those socio-moral and spiritual values that Islam stands for. More precisely, it was an instrument or a strategy through which the Prophet (SAW) realized his prophetic mission. In fact, Islam is deemed to permeate the entire gamut of our life and manifest itself not only in the mosque but also in the market place, in the schools and universities, in the courts and in battlefields. The issue would become amply clear if we understand that Islam is essentially addressed to the human heart and is supposed to cultivate in him a specific psycho-moral attitude, an attitude of submission to God and service to the humankind. In short, Muslims are enjoined to establish good governance through a just sociomoral order (or a state) wherein they could organise their individual and collective life in accordance with the teachings of the Qur’an and the Sunnah of the Prophet (SAW). It is the expectation of the Qur’an that its adherents would either reform the earth (by eradicating 17 corruption, exploitation, injustice and evil) or lay their lives in this process. There are no other (honourable) alternatives for them. They are enjoined to do justice as it is nearest to piety(taqwa). They are admonished to be careful lest the enmity of the community (or of a person)deter/hinder them from being just, fair and upright. This is the foremost obligation of the Muslims in general and the functionaries of an Islamic State in particular.It is true that Mecca and/or Madina, the cities of the Prophet of Islam (SAW), were not industrial centers but they were positively renowned commercial centers of the era. They were located on the international trade routes and were truly well known hubs of the business world. Professional integrity and moral uprighteousness are pivotal ingredients for good governance in business as was the case for the Prophet (SAW) and his family. It does not matter whether it is the home, an office, an organisation, business, state or Government, one can hardly overlook the radical and revolutionary element, that is, the involvement of women in good governance. Islam emancipated women, right from its inception, and acknowledged their rights – right to life, right to liberty, right to equality before Law, right to education, right to inheritance (or property), right to run a business and make a decent living, right to marriage and divorce and run a family life in accordance with the injunctions of Islam, right to free thinking and free expression including the right to differ even with the personal rulings of the Prophet (SAW) and his righteous caliphs (may Allah be pleased with them). These provisions sound truly revolutionary, especially when we examine them in the light of socio-moral consideration rather than cheap labor and exploitation. Business management, in our view, is a miniatural form of state management or governance. Islam insists that our business transactions should be based on fair play and justice.We must ensure just treatment and treat humans as humans. Islam requires that capital and consumer goods should remain in circulation. Healthy and fair economic activity is indeed the lynchpin of the community or the state. Unless we are committed to the establishment of financial justice, we cannot promote peace and harmony in a society. Islam insists that our business deals/ transactions should be put to writing in the presence of the witnesses, and if there are any disputes, the matter may be referred to the courts of law for proper adjudication.After this brief preamble, let us now turn to our main problem of finding some guidelines for good governance in Islam. If our presumption is not faulty, we can identify these principles with relative ease and comfort. Our contention is that the administration/governance of an organisation is analogous to the administration/ governance of the state. In fact, principles regulating the conduct of both are essentially the same.